Analisis WMA Pada Forcasting Persediaan Bahan Bangunan di CV. Edt Group - Netika Netika (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
The development of information technology from year to year always experiences very rapid development. The number of convenience facilities caused by the development of information technology has a direct impact on organizational activities.With a forecasting information system, the supply of cement, bricks and zinc will be more effective and efficient, in order to achieve development targets with information technology tools. The information technology tool in question is forecasting or Forcasting using the Weighted Moving Average Method. Through the application of this method, researchers will process and predict the inventory of building materials, with this method taking based on previous historical data at the research location, namely CV. Edt Group Keywords— Forecasting, Weighted Moving Average, Building Material Inventory